2012
DOI: 10.4028/www.scientific.net/msf.706-709.1811
|View full text |Cite
|
Sign up to set email alerts
|

Equal Channel Angular Pressing of Cu-Al Bimetallic Rod

Abstract: Coextrusion and corolling are the major processes to produce bimetallic rods, tubes and wires, the objective being to perform clad metals, bimetallic joints or seals. The aim of the present work is to produce bimetallic rods showing an ultrafine grained microstructure with enhanced properties. Bimetallic Cu-Al rods were deformed by equal channel angular pressing (ECAP) in order to study their microstructure. ECAP is an interesting process for producing bulk materials with refined microstructure and, consequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Currently, bimetallic materials representing a combination of metals or alloys with different physical and mechanical properties are widely used in various industries around the world [1][2][3]. The metal products obtained from these materials, including rods and wire, determine the safety and reliability of the functioning of railways, telephone wires, cables, objects of the defense industry, aviation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, bimetallic materials representing a combination of metals or alloys with different physical and mechanical properties are widely used in various industries around the world [1][2][3]. The metal products obtained from these materials, including rods and wire, determine the safety and reliability of the functioning of railways, telephone wires, cables, objects of the defense industry, aviation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the co‐extrusion using the equal channel angular pressing process were already performed on the material combinations Al99.95–Cu99.95 and the magnesium alloy AZ31–Al99,95 . It was shown that with both material combinations simple compound profiles with the equal channel angular pressing process could be produced.…”
Section: Introductionmentioning
confidence: 99%